Cosmeceuticals in menopausal women skin care - Wojnowska, Dorota (Menopause Review/Przegląd Menopauzalny, 2011)
The term “cosmeceuticals” was introduced by dermatologist Albert Kligman more than 25 years ago to define more active cosmetics with drug-like or therapeutical effects. Cosmeceuticals are dedicated to specific esthetic skin problems, for example wrinkles or hyperpigmentation. Mature skin showing signs of hormonal aging needs cosmetics with active ingredients which act protectively and improve appearance. Cosmeceuticals are typically claimed to deeply moisturize and regenerate skin by beneficial ingredients: retinoids, hydroxy acids, antioxidants, depigmenting agents, botanical extracts, growth factors, fitoestrogens and peptides. The text discusses and focuses on the most important groups of active agents reversing skin aging symptoms.